Outage Probability of Cognitive DF Relay Systems over Nakagami-m Fading - Dong Qin (Journal of Electrical and Computer Engineering)
This paper aims to derive accurate outage probability expressions of a cognitive decode-and-forward (DF) relay system over the Nakagami-m fading channel. A secondary system and a primary system coexist in a spectrum sharing the environment. In order to protect the data transmission of the primary system, the transmission power of the secondary system cannot exceed the tolerable interference threshold of the primary system and its available peak power. In particular, we also consider the impact on the secondary system when the primary system turns on its transmitter. Simulation results align with our theoretical formulas very well.